Biologically active secondary metabolites from medicinal plants / Julenah Ag Nuddin ... [et al.] - Ag Nuddin, Julenah; Lo, Chor Wai; Jasnie, Farnidah; Salim, Fatimah; Md Buang, Matsain (Univerisiti Teknologi MARA, Sabah, 2021)
Plants have sustained the life of man since the beginning of the time. Their functionalities go beyond being wood for fire, instead, they are able to protect, provide and nourish. The many purposes of plants have been described by many. In this article, we will describe functional plants through the chemical perspective particularly the biologically active secondary metabolites. The initiatives in natural products studies can be traced to the early years of man when plants were used for health and treatment management as documented in traditional materia medica. In modern days, numerous phytochemicals have become the main ingredients in drugs, foods, cosmetics and many more after detailed and rigorous research programs which determine their safety and efficacy. In Malaysia, and Sabah in particular, efforts are planned and carried out to identify potential traditional plants that will be beneficial in their truest forms.